Estudio de la Prueba de la Causal de Divorcio por Adulterio en el Divorcio Controvertido por Atentar el Derecho a la Intimidad y la Discriminación a la Familia - Oviedo Garzón, Maribel del Cisne (2023)
The marriage is a legal institution with the main objective to strengthening and protecting the family, because is the societies’ and State’s base. This one is based on the free will to collapse it between the parts an accomplish some demands establish by the law, and moral society, one of them is the monogamy. Thus, the rupture of this obligation through the adultery makes that the non- observance of that obligation. This conceptual fact makes the performance in a sexual relationship of the individual that has this marriage bond with another person, that is not his/her partner. The Ecuadorian Legislation, takes this fact like one of the causes to obtain a divorce, as a result, during the development of the process the proof must be applied with the main objective to establish the true of this type of event, this implies the sexual practice even the orientation to the person who did it. This involves an infringement to the right of the person, also an infringement to the families intimacy. In this way through the present work that search to determine the legal implications as result of applied the adultery proof in the legal process against the rights recognize in the Constitution and the block of constitutional human rights, especially the ones which refers to the individual and familiar intimacy